2002
DOI: 10.2337/diabetes.51.4.1172
|View full text |Cite
|
Sign up to set email alerts
|

Caspase Activation in Retinas of Diabetic and Galactosemic Mice and Diabetic Patients

Abstract: Apoptosis of retinal capillary cells begins early in diabetes and likely contributes to the capillary obliteration that is an important feature of diabetic retinopathy. Caspases are proteolytic enzymes that are closely involved in the induction and execution phases of apoptosis, but their role in the development of diabetic retinopathy has not been studied previously. Our study focused on the measurement of activities of multiple caspases in retinas of mice at different durations of diabetes. Several caspases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 181 publications
(149 citation statements)
references
References 43 publications
9
138
1
1
Order By: Relevance
“…Tissue Culture-Rat Retinal Mü ller Cell Line (rMC-1)-rMC-1 have previously been characterized and established by others and us as a useful tool for retinal Müller cell studies (4,41,42). rMC-1 were maintained in normal (5 mM) glucose Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum and 1% penicillin/streptomycin at 37°C and 5% CO 2 in a humidified incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue Culture-Rat Retinal Mü ller Cell Line (rMC-1)-rMC-1 have previously been characterized and established by others and us as a useful tool for retinal Müller cell studies (4,41,42). rMC-1 were maintained in normal (5 mM) glucose Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum and 1% penicillin/streptomycin at 37°C and 5% CO 2 in a humidified incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperglycemia-induced apoptosis has been observed in vitro on many endothelial cell types and in vivo in animal models of diabetes and the retinas of diabetic patients (40,41). The mechanisms by which hyperglycemia induces apoptosis are not fully characterized.…”
Section: Diabetes Vol 53 March 2004mentioning
confidence: 99%
“…It has been shown that in pericytes, but not in endothelial cells, apoptosis is the consequence of nuclear factor-B activation (42). In vitro, the effector mechanism of increased apoptosis in endothelial cells has been shown to be the direct activation of caspases (41), an event that was prevented in vitro by incubation with an activator of AMP-kinase (43). It has been shown in vitro that hyperglycemia decreases endothelial cell proliferation (44) and that endothelial progenitor cells isolated from diabetic patients exhibit impaired proliferation, adhesion, and incorporation into vascular structure (45).…”
Section: Diabetes Vol 53 March 2004mentioning
confidence: 99%
“…Hyperglycemia also induces the production of pro-inflammatory cytokines by Müller cells. Thus, Müller cells are a potent source for pro-inflammatory cytokines and might play a crucial role in retinal inflammation associated with the development of diabetic retinopathy [21][22][23][24][25][26]. Cytokine secretion by Müller cells influences function and viability of surrounding retinal cells, such as the retinal endothelial cells, in a paracrine fashion and their own function and viability in an autocrine manner [22].…”
Section: Introductionmentioning
confidence: 99%